2011
DOI: 10.1111/j.1600-0501.2011.02182.x
|View full text |Cite
|
Sign up to set email alerts
|

The biological response to three different nanostructures applied on smooth implant surfaces

Abstract: The three different CaP coatings with nanostructures on the implant surfaces had enhancing effects on osseointegration. Along with the surface nanotopography, the CaP chemistry might have influenced the biological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 35 publications
0
53
0
2
Order By: Relevance
“…All implants were sandblasted and acid etched (Aadva surface, GC Dental, Tokyo Japan). Half of the implants (HA) were coated with nano-sized HA according to the Promimic HA nano ™ method (Jimbo et al, 2012). The other half of the implants were subjected to only heat treatment in the same manner as the HA implants (HT).…”
Section: Implant Surface Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…All implants were sandblasted and acid etched (Aadva surface, GC Dental, Tokyo Japan). Half of the implants (HA) were coated with nano-sized HA according to the Promimic HA nano ™ method (Jimbo et al, 2012). The other half of the implants were subjected to only heat treatment in the same manner as the HA implants (HT).…”
Section: Implant Surface Preparationmentioning
confidence: 99%
“…Further, compared to the traditional 'thick' HA coatings, which generated clinical problems (Albrektsson, 1998), the mono-layered thin HA-coating seems to be stable and shows no signs of foreign body reaction (Jimbo et al, 2012). In a previous study observing the gene expression around turned-nano HAcoated implants, the nano HA-coating significantly enhanced osteogenic gene expression while increasing osteoclastic activity suggesting the nano HA is actively involved in the bone formation (Jimbo et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent in vivo studies have shown that nanostructured implant surfaces enhance bone responses, as measured both histologically and biomechanically (Bjursten et al, 2010;Jimbo et al, 2011b). The beneficial effects of these alterations may stem from conversion of the material to a highly bioactive state because of modifications at the nano level (Goransson et al, 2006;Frojd et al, 2011), which is the core concept of the biologically inspired biomimetic engineering (Flammang and Porter, 2011).…”
Section: Introduction Tmentioning
confidence: 99%